2017
DOI: 10.1039/c7ra05925f
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient FRET from aggregation-induced emission to BODIPY emission based on host–guest interaction for mimicking the light-harvesting system

Abstract: A novel highly efficient FRET system from aggregation-induced emission to BODIPY emission based on the host–guest interaction for mimicking a light harvesting system was disclosed with a FRET efficiency up to 93%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…In 2017, Ye et al reported a highly efficient FRET process from aggregation-induced emission to BODIPY emission based on hostguest interaction for mimicking the LHS [46]. In this work, AIE luminogen tetraphenylethene (TPE) was chosen to combine with crown ether moieties as a host (M1) and energy donor in FRET system (Scheme 1).…”
Section: Lhss Constructed By Crown Ethersmentioning
confidence: 99%
“…In 2017, Ye et al reported a highly efficient FRET process from aggregation-induced emission to BODIPY emission based on hostguest interaction for mimicking the LHS [46]. In this work, AIE luminogen tetraphenylethene (TPE) was chosen to combine with crown ether moieties as a host (M1) and energy donor in FRET system (Scheme 1).…”
Section: Lhss Constructed By Crown Ethersmentioning
confidence: 99%
“…In contrast to the aforementioned examples of the pH‐responsive supramolecular polymers or complexes, a pH stable fluorescence resonance energy transfer (FRET) system has been constructed for mimicking light harvesting based on the host–guest interaction between crown‐ether modified TPE as a FRET donor and boron‐dipyrromethene (BODIPY) as the energy acceptor bearing benzylamino group and triazole unit as two binding sites . FRET is an electrostatically intermediated energy transfer process.…”
Section: Aie‐active Supramolecular Nanocomplexes/polymersmentioning
confidence: 99%
“…Photochromic molecules have attracted considerable attention due to their potential applications in optical memories, , molecular switches, , and super-resolution imaging. Dithienylethene (DTE)-based photochromic derivatives have been extensively studied because of their thermal bistability and fatigue resistance enabling nondestructive readout for optical memories. To realize a nonvolatile optical memory, several methods have been proposed, such as readout with IR absorption, optical rotation, supramolecular conformational changes, and fluorescence switching. , Fluorescence quenching of DTE-based photochromic derivatives is attributed to two mechanisms: fluorescence resonance energy transfer (FRET) and photoinduced electron transfer (PET). DTE-based photochromic derivatives can obtain reversible photochromism and fluorescence switching via FRET with a high fluorescence on/off ratio and fatigue resistance . However, FRET inherently induces the photochromic reverse reaction of the ring-closed form to the ring-open one during fluorescence readout. , Thus, such systems are detrimental to nonvolatile optical memories due to the crosstalk between reading and writing/erasing wavelengths.…”
Section: Introductionmentioning
confidence: 99%